2015
DOI: 10.1371/journal.pone.0122077
|View full text |Cite
|
Sign up to set email alerts
|

Insect-Inspired Navigation Algorithm for an Aerial Agent Using Satellite Imagery

Abstract: Humans have long marveled at the ability of animals to navigate swiftly, accurately, and across long distances. Many mechanisms have been proposed for how animals acquire, store, and retrace learned routes, yet many of these hypotheses appear incongruent with behavioral observations and the animals’ neural constraints. The “Navigation by Scene Familiarity Hypothesis” proposed originally for insect navigation offers an elegantly simple solution for retracing previously experienced routes without the need for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…The hypothesis appears congruent with 61 numerous behavioral observations [29][30][31][32][33][34][35][36]. Furthermore, there are now robots and 62 simulated agents that navigate autonomously via familiarity [1,18,[37][38][39], and some 63 studies [40, 41] have suggested how neural tissue, such as the central complex and 64 mushroom bodies [42-51], might be organized to accommodate familiarity-based 65 navigation. 66 June 10, 2020 5/34Navigation by familiarity with a local sensor 67In this paper, we consider the hypothesis that the dense fields of peg sensilla on pectines 68 are analogous to the tightly packed ommatidia in compound eyes, detecting matrices of 69 chemical and textural information that are used for navigation by familiarity.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…The hypothesis appears congruent with 61 numerous behavioral observations [29][30][31][32][33][34][35][36]. Furthermore, there are now robots and 62 simulated agents that navigate autonomously via familiarity [1,18,[37][38][39], and some 63 studies [40, 41] have suggested how neural tissue, such as the central complex and 64 mushroom bodies [42-51], might be organized to accommodate familiarity-based 65 navigation. 66 June 10, 2020 5/34Navigation by familiarity with a local sensor 67In this paper, we consider the hypothesis that the dense fields of peg sensilla on pectines 68 are analogous to the tightly packed ommatidia in compound eyes, detecting matrices of 69 chemical and textural information that are used for navigation by familiarity.…”
supporting
confidence: 57%
“…When they have different 172 chemical identities, the summand is the sum of their concentrations. This yields the 173 intuitive result that there is a bigger difference between a high concentration of sensors in [1,37,52]. In an effort to increase realism, some researchers [1,28,40] The code for our model and visualizations is open-source and publicly available [56]; 183 details on its optimized implementation can be found in section 4 of S1 Appendix.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental information accesses the appropriate stored neural engram and links the appropriate scene sequence. We recently used a scene familiarity based approach to develop a simple algorithm for recapitulating complex routes in a visual information landscape obtained from 2D images from a downward facing field of view (satellite) set to approximately 250 meters above the Earth [ 18 ]. This approach successfully recapitulated routes using visual information not only from complex landscapes such as cities, but also from areas with much less visual information such as lakes and deserts.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, successful recapitulation of learned routes in simulated scenes was related to several factors, including sensor resolution, distance of objects/information from sensor, degree of navigational rotation, and the amount of visual information within the landscape [ 15 , 16 , 18 20 ]. However, there is a dearth of information detailing the interplay between these factors and navigation success in natural environments.…”
Section: Introductionmentioning
confidence: 99%